The photographer's guide to drones - Smith, Colin, 1966- (ROCKY NOOK, 2022)
Learn to master your drone--the gear, the technique, the photography, the video--and create jaw-dropping visuals! Over the last few years, drones and quadcopters have become the hottest new gear in photography, whether you're a professional photographer or an amateur shooter. These "flying tripods" have given photographers the ability to place their cameras virtually anywhere they want, creating still images and video footage that was previously impossible to capture. Many photographers have a drone or quadcopter right at the top of their "I want" list. And many others have already purchased a drone but haven't mastered its use yet. No matter what model you may own--whether that's a popular Mavic, Mini, Air, or Phantom from DJI, or another brand--you need to learn how to put this new gear to good use in your aerial photography. You need to learn how to safely operate and fly a drone, how to create compelling photos and video, and how to make your work stand out from the crowd. In this fully updated and revised edition of the bestselling first edition, photographer and bestselling author Colin Smith guides you toward mastering your drone and creating powerful and impactful imagery. Featuring his award-winning and beautiful aerial photography throughout the book, Colin will teach you: • How to fly a drone, including practice flight patterns and controller tips that will help you master the basics • New rules of composition for aerial photography as they apply to drone and quadcopter imagery • How to create the best files for both still photos and video • Post-processing techniques--both basic workflow and advanced techniques--unique to aerial photography that you need to know, such as how to make videos look both dynamic and smooth You'll learn everything you need to know about drones and quadcopters in order to take your photography to new levels...literally! Table of Contents Chapter 1: Safety and Regulations Chapter 2: Drones and Gear Chapter 3: Flight School Chapter 4: Shooting Photographs with a Drone Chapter 5: Shooting Video with Drones Chapter 6: Basic Photo Workflow in Lightroom or ACR Chapter 7: Advanced Photo Editing Chapter 8: Editing Aerial Video Parting Words Index.